Guiding Occlusal Development with Functional Appliances - Nielsen Ib Leth (Sciendo, 1996)
Functional appliances have been used in Orthodontics since their introduction by Pierre Robin almost one hundred years ago, however, our uderstanding of how they bring about orthodontic correction is still limited. This article is a brief overview of their history, mode of action, advantages and disadvantages, and includes the results of a study of attempts to control and minimise their side-effects using a recent devleopment in functional appliances: the 'Teuscher Appliance'. This appliance combines a high-pull headgear witb the activator, and is designed to reduce the often reported side-effects of functional appliances. The skeletal and dentoalveolar effects of treatment with the Teuscher Appliance on 40 consecutivelv-treated patients are reported and illustrated with four individual case reports. The results showed that the skeletal effect on the maxilla was a retardation of the normal forward and downard growth in 80 per cent of the cases, and that mandibular growth in 70 per cent of cases was forward. In patients whose mandibular growth was primarily in a vertical direction, such growth could be ascribed mainly to posterior rotation of the maxilla and/or the fact that the acrylic covering the lower posterior teeth to correct a deep bite was removed, promoting the eruption of these teeth and increasing the anterior vertical development. The dentoalveolar changes were characterised by retroclination of the maxillary incisors in 90 per cent of the patients, and were due to insufficient torque control bv the built-in torque springs, which need further development. The mandibnlar incisors were well controlled by capping. The statistical analysis showed an inverse correlation between the initial incisor inclination and the change during treatment. This suggests that proclination of the lower incisors, as previously reported, is not a contraindication to functional appliance treatment. provided the appliance is correctly designed. Overall, this study showed considerable individual response to treatment, and that the occlusal correction occurred through a combination of skeletal and dentoalveolar changes.